2022
DOI: 10.3389/fmed.2022.897188
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-specific deletion of miR-146a increases podocyte injury and diabetic kidney disease

Abstract: Diabetic glomerular injury is a major complication of diabetes mellitus and is the leading cause of end stage renal disease (ESRD). Healthy podocytes are essential for glomerular function and health. Injury or loss of these cells results in increased proteinuria and kidney dysfunction and is a common finding in various glomerulopathies. Thus, mechanistic understanding of pathways that protect podocytes from damage are essential for development of future therapeutics. MicroRNA-146a (miR-146a) is a negative regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Interactions enriched in Wt1 +/+ glomeruli included TGF-β signalling through integrin β8 ( Tgfb1-Itgb8 ), required for the release of the mature TGF-β peptide 55 and Nectin2-Nectin4 , involved in the trans-cell endocytosis of cytoplasmic cargo 56 , although neither has been investigated in the glomerulus. In Wt1 R394W/+ glomeruli, Adam17-Erbb4 was enriched, which is involved in the regulation of EGF signalling and recently implicated in glomerular injury in murine models of diabetic nephropathy 57 .…”
Section: Resultsmentioning
confidence: 95%
“…Interactions enriched in Wt1 +/+ glomeruli included TGF-β signalling through integrin β8 ( Tgfb1-Itgb8 ), required for the release of the mature TGF-β peptide 55 and Nectin2-Nectin4 , involved in the trans-cell endocytosis of cytoplasmic cargo 56 , although neither has been investigated in the glomerulus. In Wt1 R394W/+ glomeruli, Adam17-Erbb4 was enriched, which is involved in the regulation of EGF signalling and recently implicated in glomerular injury in murine models of diabetic nephropathy 57 .…”
Section: Resultsmentioning
confidence: 95%
“…Worthy of note, additional miRNAs pathogenically linked to DN have been suggested as novel promising early biomarkers. Evidence on animal models and adult subjects with T2D demonstrated an inverse correlation of miRNA 146a expression with glomerular damage, suggesting a potential protective role for podocytic miR-146a in DN development [ 79 , 80 ]. Similarly, circulating miRNA-130b levels were found to be reduced in patients with a more pronounced decrease in the subgroup with microalbuminuria [ 81 ], Besides, upregulation of miRNA-424 expression was found to reduce pathological renal changes (e.g., cellular apoptosis) occurring in DN [ 82 ].…”
Section: Evidence On the Role Of Mi-rnas 25 -93 -210 -29 And -192 In ...mentioning
confidence: 99%
“…In this study, Wang et al found that MAMs are rich in inflammatory response miRNAs in human and rat brains, including miR-146a, miR-142-3p and miR-142-5p 120 . Coincidentally, miR-146, miR-142-3p, and miR-142-5p have been shown to play a regulatory role in the progression of DKD inflammation 121 - 123 . Therefore, there is a possibility that MAMs participate in the inflammatory response of DKD through miRNAs.…”
Section: The Role Of Mam In Dkdmentioning
confidence: 99%